If (3 X + 1 ÷2 ) (3X -1 ÷2 ) is equal to 9 X square - p then the value of p is
Answers
Answered by
2
Here is the solution
Hope this helps u
Attachments:
![](https://hi-static.z-dn.net/files/d24/8142a818c409b4d402572013dcae93bf.jpg)
Answered by
2
(3x+1/2)(3x-/2) = 9xsquare -p
(3x) square-1square / 2 square = 9x square -p
9x square -1 /4 = 9x square - p
-1/4 = - p
so, the value of p is 1/4
Similar questions
Math,
1 month ago
Math,
1 month ago
English,
3 months ago
Computer Science,
3 months ago
Social Sciences,
11 months ago
Science,
11 months ago